Answer:
[tex]M=-\frac{d^2F}{kn}[/tex]
Please look at what I assumed your equation was: [tex]F=-\frac{kMn}{d^2}[/tex].
Step-by-step explanation:
I'm going to pretend that says:
[tex]F=-\frac{kMn}{d^2}[/tex].
Please correct me if I'm wrong.
We want to solve for M.
The very first thing I'm going to do is multiply both sides by [tex]d^2[/tex].
[tex]d^2F=-kMn[/tex]
Now I'm going to divide both sides by -kn:
[tex]\frac{d^2F}{-kn}=\frac{-kMn}{-kn}[/tex]
Simplifying:
[tex]\frac{d^2F}{-kn}=M[/tex]
Sometimes people don't like the negative on bottom; just move it to the center:
[tex]-\frac{d^2F}{kn}=M[/tex]
[tex]M=-\frac{d^2F}{kn}[/tex]